Histopathological Evaluation of Gastro Protective Effect of Trigonella Foenum Graecum Seed (Methi) and omeprazole in Experimentally Induced Gastric Ulcer in Rats - Afroz, Rumana; khan, Md Ismail; Rahman, Kazi Afzalur; Lotus, Mahbuba Jahan; Shahabuddin, Mir muhammad Shoyeb; Afrin, Tasnin; Yeasmin, Nahid; Moon, Kawsar Jahan (Journal of Dhaka Medical College, 2020)
Context: Peptic ulcer is a common disorder of the stomach and duodenum. Bangladesh is a developing country with a very high point prevalence of duodenal ulcer disease (11.9%) and a H. pylori prevalence of more than 90% in asymptomatic adults and 80% in children at the age of 5 years. The multifactorial pathogenesis of peptic ulcers is secretion of gastric acid. The main therapeutic target is the control of this secretion using antacids, H2 receptor blockers (ranitidine, famotidine) or proton pump blockers (omeprazole and lansoprazole). However, nowadays, gastric ulcer therapy faces a major drawback because most of the drugs currently available in the market show limited efficacy against gastric diseases and are often associated with severe side effects. Thus, there is an urgent need to identify more effective and safe antiulcer agents. In this context, the use of medicinal plants for the prevention and treatment of different pathologies is in continuous expansion worldwide. From the ancient time, various plants were used in traditional medicine with reputation as efficacious remedies. The list of plant derived modern medicine is very long now. About 33% of the drugs produced in the developed countries are derived from plants. Trigonella foenum-graecum (Fenugreek, Methi) is one of them used in many parts of world. Preliminary study on animal showed that Trigonella foenum-graecum seed has significant gastro-protective effect. A study was carried out to demonstrate the gastro-protective effect of aqueous extract and ethanolic extract of Trigonella foenum-graecum seed (Fenugreek, Methi) and omeprazole on ethanol induced gastric ulcer in experimental rats. Material and Methods: The present study was performed on 24 (twenty four) rats which were divided randomly into 4 groups each having 6 rats in the Pharmacology Department of Dhaka Medical college, Dhaka. 1 ml of absolute ethanol (5ml/kg body wt.) was orally administered to all groups by gastric intubations to induce gastric ulcer in all groups except normal control. Omeprazole suspension (20mg/kg body wt) was used as synthetic anti ulcer drug in study. Aqueous and ethanolic extract of Trigonella foenum-graecum seed(500mg/kg body wt) were used respectively orally. Histopathological analysis was carried out to evaluate the gastroprotective activity of aqueous and ethanolic extract of Trigonella foenum-graecum seed and omeprazole on ethanol induced gastric ulcer in experimental rats. Result: Pretreatment with aqueous and ethanolic extract of Trigonella foenum-graecum seed (500mg/kg/body wt) showed very significant prevention in ethanol induced gastric ulcer. Results of the study showed that in case of ethanol treated rats gross examination showed a large amount of haemorrhagic lesions confined mostly in the gastric corpus. Histologically lesion involved about two-third of the mucosa layer and exfoliation of the mucosal cells was detected. Meanwhile, red blood cells were present in the gastric mucosa and edematous submucosa was discovered. However aqueous and ethanolic extract of Trigonella foenum-graecum seed significantly reduced the haemorrhagic lesions, tissue proliferation, infiltration of cells and sloughing induced by ethanol. This prevention was statistically very significant (P<0.001). Conclusion: The aqueous and ethanol extracts of Trigonella foenum-graecum seed and omeprazole possess gastro protective properties. J Dhaka Medical College, Vol. 28, No.1, April, 2019, Page 67-75